Effect of Drilled Seeding and Nitrogen Rate on Grain Sorghum Yield in Southwest Kansas - A. J. Foster; A. Schlegel; I. B. Cuvaca; J. D. Holman; I. A. Ciampitti; C. Thompson; D. Ruiz Diaz; R. Currie (Kansas Agricultural Experiment Station Research Reports, 2018)
Drilled sorghum is normally done at the super-high population at row spacing between 7.5 and 10 inches, compared to rows planted at the spacing between 15 and 30 inches. Thompson (1983) growing super-thick sorghum at the Hays Research Station from 1974-1977, found that sorghum planted in narrow rows (12-18 in.) often produced higher yields than when planted in wide rows (24-40 in.). Norwood (1982) in Garden City repeated Thompson’s work and also came to the conclusion that yield of high population narrow row sorghum could exceed that of the low population-wide row when subsoil moisture and precipitation were adequate. The conclusion from the work of Thompson and Norwood was that subsoil moisture and precipitation was big drivers for the high population, narrow-row sorghum to equal or exceed the yield of the low population-wide row. Since then, most researchers have found yield response to plant population to be variable depending on the environment. Overall, the general consensus is that under conditions of adequate moisture, the yield of high population sorghum can continue to increase, but can decrease under dry conditions. Today moisture still remains the key for successful dryland sorghum production in southwest Kansas. Thus, the very familiar saying, “moisture and fertility are joined at the hip.” Thompson’s and Norwood’s work did not evaluate narrow row at population under 25,000 seeds/A and at a spacing below 10 in. We hypothesized that drilled sorghum at lower population could make better use of water resources and produce similar yields to drilled sorghum at higher population, and planted sorghum at the same population. Thus, the objective of this study is to evaluate drilled sorghum at different populations ranging from 20,000 to 80,000 seeds/A at a row spacing of 10 in. or less at different nitrogen rates. Furthermore, most farmers in southwest Kansas own both a drill and a planter. Thus, it is not just an agronomic issue, but it is also about getting better value from a single piece of equipment in an already economically challenging wheat-sorghum-fallow production system.
Keywords: grain sorghum; drilled seeding; nitrogen rate; southwest Kansas